2007
DOI: 10.1177/1074248407306906
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Acute Amiodarone and Dronedarone on Epicardial, Endocardial, and M Cells of the Canine Ventricle

Abstract: Amiodarone (AM) is an antiarrhythmic agent widely used in the treatment of ventricular and supraventricular arrhythmias. Dronedarone (DR) is a new compound with a pharmacological profile similar to that of AM, but iodine free. We previously demonstrated that chronic AM treatment reduces transmural dispersion of repolarization (TDR) in the canine heart. We used standard microelectrode technique to evaluate the effects of acute AM (100 microM) and DR (30 microM) on epicardial (EPI), endocardial (ENDO), and M reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Acute dronedarone has been reported to produce variable but a generally small or no effect to alter APD (1216). In rabbit superfused cardiac preparations, acute dronedarone abbreviated APD in both atria and ventricles (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Acute dronedarone has been reported to produce variable but a generally small or no effect to alter APD (1216). In rabbit superfused cardiac preparations, acute dronedarone abbreviated APD in both atria and ventricles (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…25 Similarly, dronedarone reduced transmural dispersion of repolarization and abolished d-sotalol-induced early afterdepolarizations in canine left ventricular tissue slices. 38 Thus dronedarone has multichannel blocking properties comparable to those of amiodarone. It is a more potent blocker of peak sodium current and I K-Ach currents and has stronger in vitro antiadrenergic effects compared with amiodarone.…”
Section: Electrophysiological Properties Of Dronedarone In Vitro Expementioning
confidence: 99%
“…In canine cardiac papillary muscle preparation, acute effect of dronedarone (0.1–10 µ mol/ l ) shortened action potential duration (APD), whereas the sustained effect did not alter APD [37]. In canine left ventricular Purkinje fibers and tissue slices, dronedarone lowered the incidence of triggered activities [22, 37]. Only a few studies have reported the dronedarone effects on QT and QTc intervals in healthy and complete AV block dogs [26, 37, 38].…”
mentioning
confidence: 99%